Advancing Arabic Linguistics Learning Through Technological Intervention: A Rule-Based System for Syntactic and Morphological Analysis: Memajukan Pembelajaran Linguistik Arab Melalui Intervensi Teknologi: Sistem Berbasis Aturan untuk Analisis Sintaksis dan Morfologi - Teguh Hidayanto; Nira Radita; Meivi Kartikasari (Academia Open, 2023)
This research aims to accelerate the understanding of Arabic linguistics by developing a system that enhances the learning experience for beginner and intermediate level students. The system employs a basis rule approach, drawing from classic Arabic grammar books, to analyze word structure errors in phrases, clauses, and sentences. The study successfully implemented the system, achieving compatibility between inputs and outputs as confirmed through blackbox testing. Moreover, expert validity tests validated the system's accuracy in detecting grammatical errors. The implications of this research highlight the potential of technological intervention in improving language learning processes, facilitating better comprehension and proficiency in Arabic linguistics. Highlight: Enhanced Learning Experience: The research develops a system to accelerate Arabic linguistics understanding for beginner and intermediate students, providing a more effective and efficient learning experience. Basis Rule Approach: Drawing from classic Arabic grammar books, the system utilizes a basis rule approach to analyze word structure errors in phrases, clauses, and sentences, aiding students in mastering the language's syntactic and morphological structure. Validated Accuracy: Expert validity tests confirm the system's accuracy in detecting grammatical errors, ensuring reliable and valuable feedback for language learners. The implications suggest the potential of technological intervention in advancing language learning processes and promoting proficiency in Arabic linguistics. Keyword: Arabic Linguistics, Language Learning, Basis Rule Approach, Technological Intervention, Grammatical Errors